Evaluation of Instagram Social Media Marketing to Plan New Strategy Formulation in Menantea - Dinanti, Maharani Putri; Soputra, Auryn Nathania; Sampurno, Griselda; Chan, Arianis (International Journal of Business Studies, 2022)
Social media allows marketers to connect and engage potential customers. This led many marketing professionals to refocus on their social media marketing strategy. Menantea Toko is one of the most talked Food and Beverage Brand in 2021. Their existence surprised the public because they gained 100k followers in just 3 days. The purpose of this research is to determine how to evaluate the usage of social media Instagram Menantea and to propose a social media marketing strategy for Menantea. This form of research is taken as descriptive quantitative research. The research population is followers of Instagram Menantea. This study used a non-probability sample approach known as purposive sampling, with the minimal sampling size obtained using the slovin formula. Methods for gathering data include in-depth interviews, surveys, and Forum Group Discussions (FGD). Pearson's product moment validity test and the Cronbach's Alpha formula were used to evaluate the questionnaire's reliability. The results demonstrated that social media marketing on Instagram Menantea was effective and generated a positive response from followers.